2017
DOI: 10.3389/fphar.2017.00649
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of SEA0400 on Ca2+ Transient Amplitude and Proarrhythmia Depend on the Na+/Ca2+ Exchanger Expression Level in Murine Models

Abstract: Background/Objective: The cardiac Na+/Ca2+ exchanger (NCX) has been identified as a promising target to counter arrhythmia in previous studies investigating the benefit of NCX inhibition. However, the consequences of NCX inhibition have not been investigated in the setting of altered NCX expression and function, which is essential, since major cardiac diseases (heart failure/atrial fibrillation) exhibit NCX upregulation. Thus, we here investigated the effects of the NCX inhibitor SEA0400 on the Ca2+ transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…The methods to isolate atrial and ventricular cardiomyocytes have been reported in former studies ( Bögeholz et al, 2016 , 2017 ). In brief, mice were euthanized by carbon dioxide inhalation and excised hearts were retrogradely perfused via the aorta using a modified Langendorff apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…The methods to isolate atrial and ventricular cardiomyocytes have been reported in former studies ( Bögeholz et al, 2016 , 2017 ). In brief, mice were euthanized by carbon dioxide inhalation and excised hearts were retrogradely perfused via the aorta using a modified Langendorff apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacological inhibition of NCX1 is generally viewed as beneficial since it reduces Ca 2+ influx during reverse mode limiting Ca 2+ overload and attenuates depolarization during forward mode reducing triggered activity ( Antoons et al, 2012 ). However, if NCX1 is already diminished as shown in many models of diabetes ( Makino et al, 1987 ; Pierce et al, 1990 ; Golfman et al, 1998 ; Hattori et al, 2000 ) additional inhibition was proven to be detrimental leading to adverse accumulation of Ca 2+ in cytosol and cell death ( Bögeholz et al, 2017 ).…”
Section: Therapeutic Strategies To Improve Ca 2+ Hmentioning
confidence: 99%
“…This differential arrhythmic effect may be dependent on the expression levels of NCX. A study found SEA-0400 to be antiarrhythmic in mouse models with increased NCX expression, such as HF and AF, but in conditions with reduced NCX expression, SEA-0400 was found to increase Ca 2+ transient amplitude and spontaneous Ca 2+ transients, ultimately acting proarrhythmic (Bogeholz et al, 2017). These findings suggest that in clinical conditions in which NCX function is reduced, such as diabetic cardiomyopathy, further NCX inhibition could trigger arrhythmias by reducing NCX function below the level required for balanced Ca 2+ dynamics (Bogeholz et al, 2017).…”
Section: Ncxmentioning
confidence: 99%